Restoration of topoisomerase 2 function by complementation of defective monomers in Drosophila. - Hohl, A.M.; Thompson, M.; Soshnev, A.A.; Wu, J.; Morris, J.; Hsieh, T.S.; Wu, C.T.; Geyer, P.K. (Genetics, 2012)
Type II topoisomerases are essential ATP-dependent homodimeric enzymes required for transcription, replication, and chromosome segregation. These proteins alter DNA topology by generating transient enzyme-linked double-strand breaks for passage of one DNA strand through another. The central role of type II topoisomerases in DNA metabolism has made these enzymes targets for anticancer drugs. Here, we describe a genetic screen that generated novel alleles of Drosophila Topoisomerase 2 (Top2). Fifteen alleles were obtained, resulting from nonsense and missense mutations. Among these, 14 demonstrated recessive lethality, with one displaying temperature-sensitive lethality. Several newly generated missense alleles carry amino acid substitutions in conserved residues within the ATPase, Topoisomerase/Primase, and Winged helix domains, including four that encode proteins with alterations in residues associated with resistance to cancer chemotherapeutics. Animals lacking zygotic Top2 function can survive to pupation and display reduced cell division and altered polytene chromosome structure. Inter se crosses between six strains carrying Top2 missense alleles generated morphologically normal trans-heterozygous adults, which showed delayed development and were female sterile. Complementation occurred between alleles encoding Top2 proteins with amino acid substitutions in the same functional domain and between alleles encoding proteins with substitutions in different functional domains. Two complementing alleles encode proteins with amino acid substitutions associated with drug resistance. These observations suggest that dimerization of mutant Top2 monomers can restore enzymatic function. Our studies establish the first series of Top2 alleles in a multicellular organism. Future analyses of these alleles will enhance our knowledge about the contributions made by type II topoisomerases to development.